Combination of ERT and EM methods in the exploration of karst caves and foundation in the Nujiang airport survey of China. Issue 1 (September 2020) - Yue, Yunbao; Guo, Ziming; Luo, Wei; Zhang, Gang; Chen, Ning
Abstract: Due to controls from karst cave, grike fissure zone, tectonic crushed zone and other defects in rock masses, the airfield runway in the karst region is easy to have collapse and leakage failure, thus resulting in runway deformation and buckling. Therefore, it is of important significance to detect rock defects in airfield runway accurately. In this study, electrical resistivity tomography (ERT) and electromagnetic (EM) were combined to detect stability of karst cave and foundation under the runway of Nujiang airport survey of China. Size, shape and scale of underground karst cave were detected accurately by setting 3 ERT measuring lines. Distribution of karst caves in shallow underground layer was disclosed and validated by drilling data. Electrical structures in deep underground layer were detected by setting 11 EM profiles. Based on 2D EM inversion and 3D modeling, it found that electrical structure in deep underground layers of the runway was dominated by high specific resistance, indicating that there's relatively complete bed rock mainly composed of limestone. Hence, the foundation showed relatively satisfying overall stability, accompanied with local distribution of low-resistance anomalies which was attributed to crushed mudstone. Research results demonstrated that the combination of ERT and EM is feasible and applicable to detect geological structural stability in karst development and deep positions beneath the runway in karst areas.